Production of bioethanol from tapioca starch using Saccharomyces cerevisiae : effects of pH and air flow rate - Muna Suhaili, Zakaria (2008)
The effects of pH and air flow rate on fermentation process for bioethanol production in 2 L bioreactor using Saccharomyces cerevisiae were studied. Other conditions such as temperature, agitation and inoculum concentration were fixed at specific values. Two-step enzymatic hydrolysis of tapioca starch by commercially available α-amylase and glucoamylase were employed at the beginning of the process for glucose production. The cell growth study was conducted in order to observe the cell growth profile in the resulted sugar. The fermentation study was conducted in aerobic condition using 2 L bioreactor with various pHs (4, 5, and 6) and air flow rates (1.0, 1.5 and 2.0 L/min). Based on the results, the optimum pH and air flow rate were pH 5 and 1.0 L/min respectively. The highest yield of ethanol was 3.64 g/L which produced at pH and air flow rate at 1.0 L/min.